Genocide and resistance Nr. 17(1) - Matulytė, Margarita; Černeckaitė, Irina; Vitkus, Hektoras; Bubnys, Arūnas; Brandišauskas, Valentinas; Skorupskas, Andrius (Genocidas ir rezistencija, 2005)
Full Issue (paper copy scan)